Nasal airway analysis using three· dimensional software among normal subjects in Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan - Ramiza Ramza, Ramli (2008)
In order to function well the nasal patency plays a major role to bring in inspired air and release the expired air. The patency of the nasal cavity can be assessed by variety of methods, ranging from simple subjective measurement such as - visual analogue scale to more accurate objective measurement such as acoustic rhinometry. Acoustic rhinometry (AR) is the recommended technique for assessment of the nasal geometry. It quantifies subjective symptoms of nasal obstruction into an objective assessment of nasal patency. 30 software is capable in converting the data from ~R (20) into a 3-Dimensional image and this will provide a new prospect in how nasal patency can be measured and evaluated. The objective of this study is to convert the normal values of the Minimal Crosssectional Area (MCA) and nasal volumes collected using Acoustic Rhinometry and analyze using the 30 software. This study also analyzed the differences between MCA and nasal volumes of male and female collected by the AR and 30 software.This is a cross sectional study of healthy volunteer adult subjects ranging between the age of 18 years old to 70 years old, comprising of 75 males and 75 females Otorhinolaryngology Head and Neck clinic, Hospital Universiti Sains Malaysia; (HUSM), Kubang Kerian, Kelantan. A written consent was taken from the candidates after the aim and methodology as wel1 as the procedure was explained to the candidates. A primary assessment with thorough history, systematic ear, nose and throat (ENn examination, including rjgid nasoendoscope was included and performed to each subjects. Later the subjects were examined using the AR scan. The AR scan that was be used was the RhinoScan SRE21 00 (RhinoMetric, Denmark). The Acoustic rhinometry was performed following the standard procedure as described in the literature. The data was analyzed using paired T -test V~fith p-value less than 0.05 was con~idered to be significant.In this study, the mean MCA 1 for males were 0.49 ± 0.14 cm2 and females 0.42 ± 0.16 cm2 . For the nasal volume of MCA, V1 for males were 3.46 ± 1.28 and for females were 2.9 ± 0.98 cm2 • In 30 analysis the results also showed that the adult male nasal airway is significantly different from female teenagers (p=O.OO), female adult (p=O.OO) and male teenager (p=0.004) on both the left and right nostril. There is also no significant correlation between MCA and BMI.The male nasal airways differ from the female nasal airways on both the left and . right nostrils. These results were produced by the Acoustic rhinometry software and also ,by the 30 software. The 3D software showed that the male adult nose differs from the female (adult and teenager) and even the male teenager. The male nasal airway is narrower at the anterior nasal valve and wider distal to nasal valve. Acoustic rhinometry is a valuable method of assessing geometry of n~sal cavity. 3-Dimensional software can be used with AR in enhancing the data and making it more useful in diagnosis, treatment planning and ongoing post treatment or surgery.